2020
DOI: 10.1007/s10528-020-10007-w
|View full text |Cite
|
Sign up to set email alerts
|

miR-491-3p is Downregulated in Retinoblastoma and Inhibit Tumor Cells Growth and Metastasis by Targeting SNN

Abstract: Retinoblastoma (Rb) is the most common pediatric malignant tumor of the eyes. Previous studies demonstrated that miR-491-3p is downregulated in various cancers. However, its function in Rb remains unknown. A total of 15 pairs of primary Rb tissues and adjacent noncancerous tissues were collected. Quantitative real-time PCR (qRT-PCR) was used to investigate the expression profiles of miR-491-3p. qRT-PCR, western blotting and in situ immunocytochemistry were performed to investigate the expression profiles of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Furthermore, miR-1207-5p as one of the ten miRNAs expressed significantly different among gastric cancer patients with or without LNM via miRNA microarray, which could serve as a useful biomarker in the prediction of LNM [ 13 ]. MiR-491-3p, a tumor suppressor miRNA, was found decreased in many solid tissues, including brain tumor [ 14 ], colorectal cancer [ 15 ], and retinoblastoma [ 16 ]. It was worth mentioning that miR-491-3p was downregulated in gastric cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR-1207-5p as one of the ten miRNAs expressed significantly different among gastric cancer patients with or without LNM via miRNA microarray, which could serve as a useful biomarker in the prediction of LNM [ 13 ]. MiR-491-3p, a tumor suppressor miRNA, was found decreased in many solid tissues, including brain tumor [ 14 ], colorectal cancer [ 15 ], and retinoblastoma [ 16 ]. It was worth mentioning that miR-491-3p was downregulated in gastric cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…HOTAIR propels carcinogenesis and shows an association with tumor initiation and progression, drug resistance, and poor survival rates of patients [ 28 ]. In previous studies concerning RB, most researchers have selected ARPE-19 cells as the control group [ 29 31 ]. The results of our study found no significant difference in HOTAIR expression between the two normal retinal cell lines ARPE-19 and RPE-1, and thus ARPE-19 cells could be utilized as the ideal control in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-491-3p exerts a tumour suppressor effect on many human malignancies, such as retinoblastoma ( Hu et al, 2021 ), osteosarcoma ( Duan et al, 2017 ), hepatocellular carcinoma (HCC) ( Zhao et al, 2017 ), and glioblastoma ( Li et al, 2015 ). MiR-491-3p expression is also decreased in CRC tissues and oxaliplatin-resistant CRC cells ( Guo et al, 2017 ; Tang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-491-3p is one of the mature products of miR-491. Recently, miR-491-3p has been reported to be involved in the progression of several cancers, such as retinoblastoma, tongue cancer, glioblastoma, and gastric cancer ( Hu et al, 2021 ; Zheng et al, 2015 ; Li et al, 2015 ; Yu & Luo, 2022 ). Furthermore, it has been demonstrated that miR-491 facilitates CRC cell apoptosis by reducing Bcl-XL expression ( Nakano et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%